Indicação Geográfica na vitivinicultura como estratégia para o desenvolvimento local e valorização de territórios: Análise da experiência ibérica (Portugal e Espanha) e da Serra Gaúcha (estado do Rio Grande do Sul - Brasil) - Teodoro, Vitor Bini [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The process of globalization has intensified competition and escalated agro-industrial production, with a strong expansion of agricultural commodities. Nevertheless, new market niches and consumers have also emerged, seeking differentiated and quality-recognized products. In this context, Geographical Indications arise, being a recognized registration conferred upon products or services that are characteristic of their region of origin, attributing to them reputation, intrinsic value, and their own identity, distinguishing them from similar ones available in the market. These are products that present a unique quality due to natural resources such as soil, vegetation, climate, and craftsmanship. In this sense, belonging to a demarcated region can become a means of integrating peripheral regions and small municipalities into the competitive agri-food market, providing their respective local populations with a solution for local development, the central hypothesis of this study. Thus, the present study sought to identify, in the selected countries (Brazil, Spain and Portugal), to understand the development of their respective geographical indications circumscribed in wine regions, in a comparative perspective, whether belonging to a region demarcated enabled the local development of these locations. It can be concluded that belonging to a demarcated region sharpens curiosity about the local peculiarity, providing relevant gains for the localities, as long as the actions occur in a cooperative and articulated way, between the Public and Private Power and Civil Society, being able to promote progressively achieve socioeconomic inclusion and improve the quality of life for their respective populations.

O processo de globalização acirrou a concorrência e intensificou a produção agroindustrial, com forte expansão das commodities agrícolas. Não obstante, novos nichos de mercado e consumidores também surgiram, buscando produtos diferenciados e de qualidade reconhecida. Nesta tangente, surgem as indicações geográficas, sendo este um registro reconhecido e conferido a produtos ou serviços que são característicos do seu local de origem, o que lhes atribui reputação, valor intrínseco e identidade própria, além de os distinguir em relação aos seus similares disponíveis no mercado. São produtos que apresentam uma qualidade única em função de recursos naturais como solo, vegetação, clima e saber fazer. Neste sentido, o pertencimento a uma região demarcada pode vir a ser um meio de inserção de regiões periféricas e pequenos municípios no mercado concorrencial agroalimentar, conferindo às suas respectivas populações locais, uma solução para o desenvolvimento local, hipótese central deste estudo. Assim, o presente estudo buscou identificar, nos países selecionados (Brasil, Espanha e Portugal), compreender o desenvolvimento de suas respectivas indicações geográficas circunscritas em regiões vitivinícolas, em perspectiva comparada, se o pertencimento a uma região demarcada propiciou o desenvolvimento local destas localidades. Pode-se concluir que o pertencimento à uma região demarcada, aguça a curiosidade pela peculiaridade local, proporcionando ganhos relevantes para as localidades, desde que as ações ocorram de forma cooperativa e articulada, entre o Poder Público e Privado e a Sociedade Civil, podendo promover progressivamente a inclusão socioeconômica e melhoria da qualidade de vida para suas respectivas populações.
Geographical Indication in wine making as a strategy for local development and appreciation of territories: Analysis of the Iberian experience (Portugal and Spain) and Serra Gaúcha (state of Rio Grande do Sul - Brazil)
Keywords: Vitivinicultura; Políticas públicas; Agronegócio; Desenvolvimento local; Pequenos munícipios